Synthesis and stereochemical assignments of diastereomeric Ni(II) complexes of glycine Schiff base with (R)-2-(N-{2-[N-alkyl-N-(1-phenylethyl)amino]acetyl}amino)benzophenone; a case of configurationally stable stereogenic nitrogen - Moriwaki, Hiroki; Resch, Daniel; Li, Hengguang; Ojima, Iwao; Takeda, Ryosuke; Aceña, José Luis; Soloshonok, Vadim A. (Beilstein Journal of Organic Chemistry, 2014)
A family of chiral ligands derived from α-phenylethylamine and 2-aminobenzophenone were prepared by alkylation of the nitrogen atom. Upon reaction with glycine and a Ni(II) salt, these ligands were transformed into diastereomeric complexes, as a result of the configurational stability of the stereogenic nitrogen atom. Different diastereomeric ratios were observed depending on the substituent R introduced in the starting ligand, and stereochemical assignments were based on X-ray analysis, along with NMR studies and optical rotation measurements.
Keywords: amino acids; asymmetric synthesis; Ni(II) complexes; Schiff bases; stereogenic nitrogen